The Effectiveness of Ethno-Pedagogy-Based Role Playing Models in Improving Language and Reading Skills in Early Childhood - Siti Sani; Kastam Syamsi; Abul Wahid; Everhard Markiano Solissa; Hasyim Mahmud Wantu; Tongam E Panggabean; Andri Kuniawan; Tomi Apra Santosa (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This study aims to determine the effectiveness of the role playing model with an ethno-pedagogical approach to early childhood language and reading skills. This study is a meta-analysis study. The inclusion criteria in this study are 1) the research must be relevant; 2) data is obtained from national or international journals indexed by SINTA or Scopus; 3) the study was published in the 2022-2024 time frame; and 4) the study must report complete data to calculate the effect size value. Analyze data with the help of JASP and Microsoft Excel applications. The results concluded that the 19 studies analyzed showed that the ethno-pedagogy-based role playing model had a significant influence on early childhood language and reading skills with a score of (g= 0.895; 95% CI 0.706-1.084; P < 0.001) high effect size category.Â  These findings explain that the ethno-pedagogical role playing model effectively improves early childhood language and writing skills in the learning process.